Technology Adoption–The Diffusion Of Mobile TV in Malaysia with Reference to The U.K. - Tan, Sean Khong (2008)
The adoption patterns for mobile services has been a key challenge for research in mobile technology applications. With the release of 3G technology in mobile communications years ago, people are wondering whether Mobile TV can be the next “killer application”. Roger’s Innovation Diffusion Theory is applied to analyze the diffusion of Mobile TV using broadcast technologies in the U.K. and Malaysia. The analysis on the former group is based on the trial results and market situation thus far while users actual trial primary survey data and interviews with operator, mobile content provider, and mobile TV solution provider for the latter. The Primary data provides Klang Valley professionals current mobile usages and their feeling, comments, and possible willingness to pay in the future. The possible barriers, challenges, threats and opportunities of the diffusion are identified. The potential business models among operators, network providers, content providers, and broadcasters are discussed.